Profil Fraksi Sitotoksik terhadap Sel Murine Leukemia P-388 dari Ekstrak Biji Honje (Etlingera elatior) - Alfindah Rusanti; Dede Sukandar; Tarso Rudiana; Adawiah Adawiah (Syarif Hidayatullah State Islamic University, 2017)
The research characterization of cytotoxic fraction against P-388 leukemia murine cells from the extract honje (Etlingera elatior) seed have been reported. This research lead to isolated and characterization of cytotoxic compounds against P-388 leukemia murine cells from the extract E. elantior seed. The extract of E. elantior seed was maserated by methanol, n-hexane, and ethyl acetate, respectively and estimated their cytotoxic activity against P-388 leukemia murine cell with 3- (4, 5-dimetiltiazol-2-yl) -2,5-difeniltetrazolium bromide (MTT) assay guided toxicity test against of shrimp Artemia salina Leach. Brine shirmp Lethality Test (BSLT) method. The active extracts will be separated by fractionation using column chromatography, radial chromatography, and for analyzing the purity of isolate will estimate by HPLC. The chemical structure of pure isolate will be identified by spectroscopies data UV Vis, FTIR, NMR and MS. The ethyl acetate extract from honje seed have cytotoxic activity by leukemia P-388 cell with IC50 19.21 µg/mL. The compound toxic as cytotoxicagainst P-388 leukemia murine cells is flavonoid compouds their is resveratrol, lapachol, apigenin, methylated chrysin, 6,2’-dihydroxyflavanone, 3-hydroxy-3,4’-dymethoxyflavone and 4’-hydroxy-5,7-dimethoxyflavanone.DOI: http://dx.doi.org/10.15408/jkv.v0i0.3640